Evaluation of high risk screening protocol for detection of overt hypothyroidism in pregnancy - Goel, Bharti; Singh, Anju; Goel, Poonam; Kaur, Jasbinder; Singla, Seema; Singla, Mandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Overt hypothyroidism is a known cause of feto-maternal morbidity. Many large-scale studies do not support the identification and treatment of sub-clinical hypothyroidism. Hence, we need a screening protocol that will identify all cases of overt hypothyroidism. The present study aimed to evaluate the high-risk screening protocol for detection of overt hypothyroidism during pregnancy. Methods: Authors performed a prospective observational study for detection of thyroid dysfunction in 604 pregnant women in a tertiary care hospital setting. Detailed demographic, medical and obstetric history was noted and baseline serum thyrotropin (TSH) level and urinary iodine levels were checked. Reflex testing for thyroid peroxidase antibody was done in women diagnosed to have hypothyroidism. The enrolled women were then grouped as high risk if any of the high-risk criteria provided by ATA was positive. Results: The study population was iodine sufficient with median urinary iodine (MUI) level of 255µg/l. Overall 32.2% women (n=201) were found to be hypothyroid (TSH >2.5mIU/L), 0.8% women (n=5) were hyperthyroid. Overt hypothyroidism was seen in 3.8% women (n=23), all of whom were in the high-risk group as per the ATA guidelines. This co-relation was highly significant (likelihood ratio 24.94; P <0.001). Sensitivity of targeted screening for detection of overt hypothyroidism was 100%. On the other hand, logistic regression analysis showed poor co-relation of high-risk factors with sub-clinical hypothyroidism (TSH levels between 2.5 mIU/L- 10.0 mIU/L), likelihood ratio being 0.534; P>0.05. Conclusions: High risk screening protocol is highly sensitive for detection of overt hypothyroidism and provides the best therapeutic payoff.